Possible methods of preventing groundwater contamination at landfill sites; case studies from Nepal - Panthee, Suman (Bulletin of the Department of Geology, 2008)
Significant increase in municipal solid waste in Nepal has led to build up of few landfill sites in urban areas. Among several problems existing in the landfill sites, groundwater and soil contamination are the major problems. The major causes of contamination are generation of leachate, improper design and selection of materials in the landfill sites. Therefore, understanding on physical and chemical behavior of the leachate with the fill material, and the landfill site design parameters is required to solve the problem. Three landfill sites (Gokarna, Sisdol and Pokhara) were studied as case studied to identify leakage problems in view of controlling leachate migration. Hydraulic conductivity, particle size distribution and shape of basement material were studied. Gokarna Landfill Site did not have proper clay lining or other technology that prevents groundwater contamination. The Sisdol and the Pokhara landfill sites were improved sites but were devoid of clay lining. To control leachate migration, proper basement and other design is required. The slope of the basement clay liner should be adjusted properly according to the hydraulic conductivity of the clay to prevent leachate movement downward. Similarly, selection of shape and size of drainage material is important for aeration, and to prevent from leachate clogging and puncturing the basal clay or geo-membrane. The case studies suggested need of some improvements for basal design of landfill sites for future. Besides the basement design, design of leachate suction well and vegetative technology for leachate treatment are necessary. A basement design is proposed that will be economic and suitable for developing countries. This paper discusses about some drawbacks in technical practices in some landfill sites in Nepal and suggests possible methods that can be applied in constructing landfill sites for reducing contamination. doi: 10.3126/bdg.v11i0.1542 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 51-60